2012
DOI: 10.1109/tdei.2012.6311489
|View full text |Cite
|
Sign up to set email alerts
|

On partial discharge measurement in dielectric liquids

Abstract: Partial discharge detection in dielectric liquids requires particular PD measurement techniques and instruments. Simultaneous partial discharge (PD) measurements that are employed on insulating liquids, using dual narrow/wide band detectors, are described. Narrow band PD detectors, which are of the integrating type are suitable for the measurement of the total charge transfer in pC of the overall discharge event. Wide band measurement techniques permit the acquisition of the discrete PD pulses in dielectric li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…Pompili et al [23] showed that negative streamers comprise of several high frequency pulses with ascending magnitude as the bubble within the fluid expands in volume. However, these pulses become integrated to a single PD event by the integration time of the PD detector (~10 s [24]).…”
Section: Discussionmentioning
confidence: 99%
“…Pompili et al [23] showed that negative streamers comprise of several high frequency pulses with ascending magnitude as the bubble within the fluid expands in volume. However, these pulses become integrated to a single PD event by the integration time of the PD detector (~10 s [24]).…”
Section: Discussionmentioning
confidence: 99%
“…It gives high local electric field stress to simulate a local PD site. Examples of applying the needle -plane electrode systems for the measurement of PDIV and PD have been reported in [10][11][12][13]. Because the electric field stress on the tested liquid greatly depends on the electrode configuration so the PDIV value of the same liquid is different when it is tested with various types or configuration of the electrode arrangement.…”
Section: Partial Discharge and Partial Discharge Inception Voltagmentioning
confidence: 99%
“…The most important are occurrence of a current pulse, emission of electromagnetic waves of ultra-high frequency (UHF), generation of optical radiation and high-energy radiation (X-/gamma rays), chemical transformations in the isolation, an elastic shock deformation and the associated acoustic wave generation. Based on these phenomena, diagnostic methods have been developed for detection, measurement and localization of PD, which may occur in insulating systems of power devices [1][2][3][4][5][6][7][8]. Currently, the assessment of electrical discharges shall apply the following non-destructive methods: electric [9][10][11][12][13], gas chromatography and acoustic emission (AE) [14][15][16][17][18][19][20] as well as the optical method [21][22][23].…”
Section: Introductionmentioning
confidence: 99%